1991
DOI: 10.1007/bf01877225
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of α-chymotrypsin-N-trifluoroacetyl-4-fluorophenylalanine complexes

Abstract: Fluorine NMR lineshape, relaxation and Overhauser effect data collected at 282 and 470 MHz have been used to obtain information about the nature of complexes formed between N-trifluoroacetyl-4-fluorophenylalanine and the enzyme chymotrypsin. Systems involving both enantiomers have been examined as well as derivatives of these in which the aromatic ring hydrogens have been replaced by deuterium. The enzyme-induced fluorine chemical shift effects and the dynamics of molecular motions of the fluorophenyl ring at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The kinetics of transient inhibitor binding to large enzymes and proteins have been studied previously utilizing mostly 19 F NMR relaxation or line shape analysis and proton NMR relaxation measurements . More recent work in this area has included the characterization of multiple conformational states in small protein−peptide complexes , and in enzyme−substrate/inhibitor interactions. It has been shown that in complex protein systems protein−ligand interactions may involve a dynamic equilibrium of an ensemble of protein−ligand complexes with related or distinctly different structural configurations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetics of transient inhibitor binding to large enzymes and proteins have been studied previously utilizing mostly 19 F NMR relaxation or line shape analysis and proton NMR relaxation measurements . More recent work in this area has included the characterization of multiple conformational states in small protein−peptide complexes , and in enzyme−substrate/inhibitor interactions. It has been shown that in complex protein systems protein−ligand interactions may involve a dynamic equilibrium of an ensemble of protein−ligand complexes with related or distinctly different structural configurations.…”
mentioning
confidence: 99%
“…13,16 Even without affinity "maturation", these specificbinding ligands can be converted into bivalent and polyvalent molecules with a potential increase in affinity and the lifetimes of the protein-ligand complexes. [15][16][17][18][19][20][21][22] The kinetics of transient inhibitor binding to large enzymes and proteins have been studied previously utilizing mostly 19 F NMR relaxation [23][24][25][26][27][28] or line shape analysis 29 and proton NMR relaxation measurements. 30 More recent work in this area has included the characterization of multiple conformational states in small protein-peptide complexes 31,32 and in enzymesubstrate/inhibitor interactions.…”
mentioning
confidence: 99%
“…In some instances, the individual peaks for bound species are clearly distinguishable (Figures 1, 2, 4-6, and 7E); in other instances, the broadened structure of the bound envelope is indicative of more than one peak in intermediate to slow exchange (Figures 3 and 7A,C). Gerig's laboratory has extensively documented similar behavior for the binding of fluorinated ligands to protein sites (23,25,(32)(33)(34)(35)(36). In our experiments, the bound resonances correspond to protein-ligand complexes with different chemical shifts, reflecting the high sensitivity of fluorine chemical shifts to small differences in microenvironment (24) (Figures 1-7), and these overlapping resonances can be decomposed into individual peaks by fitting to Lorentzianshaped transitions.…”
Section: Discussionmentioning
confidence: 59%